Process Oriented Guided Inquiry Learning (POGIL) Model: Optimizing Student Learning Interest - Siti Rohimah Maspupah; Deden Makbuloh; M. Indra Saputra (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Islamic boarding schools like MTS Walisongo, Central Lampung, succeed when students are interested in learning, especially Islamic law. Initial observations indicated that students showed little interest in learning, particularly in paying attention. This phenomenon was evident from the lack of student interaction, limited interest in the topic, and the prominence of conventional learning approaches. This study tests whether the POGIL (Process Oriented Guided Inquiry Learning) learning approach increases student interest in Islamic jurisprudence. This quantitative study was quasi-experimental and used a post-test-only control group design. Class VIII C was the experimental class, and VIII D was the control class in the research sample, obtained by simple random sampling. The POGIL model has five steps: orientation, exploration, concept invention, application, and closure. The non-test questionnaire had 16 statement items that measured student attention. The results of data analysis using the t-test showed a significant value of 0.001 (p < 0.05), indicating a significant difference between the experimental and control classes. Thus, the POGIL learning model has proven effective in increasing student interest in learning, particularly in the aspect of attention. This study concludes that the implementation of POGIL makes a positive contribution to creating an active, collaborative, and enjoyable learning atmosphere and can be used as an innovative learning alternative to improve the quality of education in madrasah environments.